2020
DOI: 10.3390/cells9081811
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Soluble Thrombomodulin Suppresses Monocyte Adhesion by Reducing Lipopolysaccharide-Induced Endothelial Cellular Stiffening

Abstract: Endothelial cellular stiffening has been observed not only in inflamed cultured endothelial cells but also in the endothelium of atherosclerotic regions, which is an underlying cause of monocyte adhesion and accumulation. Although recombinant soluble thrombomodulin (rsTM) has been reported to suppress the inflammatory response of endothelial cells, its role in regulating endothelial cellular stiffness remains unclear. The purpose of this study was to investigate the impact of anticoagulant rsTM on lipopolysacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In fact, the C-type lectin-like domain of TM, which lacks the thrombin-binding ability, inhibits the alamin high-mobility group box 1 protein [23] and lipopolysaccharide (LPS) [24] and suppresses neutrophil adhesion to endothelial cells [17], during which rTM promotes the inhibition of the mitogen-activated protein kinase pathway and activation of nuclear factor-κB [17]. Recently, Okamoto et al [25] demonstrated the mechanism underlying rTM inhibition of monocyte adhesion to endothelial cells by suppressing LPS-induced cell sclerosis in a cell stiffness-dependent manner. This may reduce endothelial in ammation and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the C-type lectin-like domain of TM, which lacks the thrombin-binding ability, inhibits the alamin high-mobility group box 1 protein [23] and lipopolysaccharide (LPS) [24] and suppresses neutrophil adhesion to endothelial cells [17], during which rTM promotes the inhibition of the mitogen-activated protein kinase pathway and activation of nuclear factor-κB [17]. Recently, Okamoto et al [25] demonstrated the mechanism underlying rTM inhibition of monocyte adhesion to endothelial cells by suppressing LPS-induced cell sclerosis in a cell stiffness-dependent manner. This may reduce endothelial in ammation and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, after cells were returned to normoglycemic conditions for several days, both endothelial stiffness and barrier integrity improved in parallel even though some stiffening and gaps persisted. Endothelial stiffening was also observed in response to lipopolysaccharide or TNFα inflammatory signals with stiff stress fibers identified both by staining and by AFM mapping and 2D rendering ( Okamoto et al, 2020 ). In this study, the integrity of adherens junctions was not evaluated but interestingly they showed that endothelial stiffening is accompanied with decreased functionality of the gap junctions, inter-cellular channels that allow passage of intracellular small molecules between adjacent cells suggesting that endothelial stiffening affects cell-cell communication/interaction via several mechanisms.…”
Section: Relationship Between Endothelial Stiffening and Barrier Func...mentioning
confidence: 99%
“…Moreover, mechanics play a role early in the immune system maturation. Recent studies have shown how substrate stiffness drives dendritic cell functions, 247 macrophage metabolism, 248 and monocyte maturation and recruitment 249,250 …”
Section: Inflammatory Diseasesmentioning
confidence: 99%
“…Recent studies have shown how substrate stiffness drives dendritic cell functions, 247 macrophage metabolism, 248 and monocyte maturation and recruitment. 249,250 Cell mechanics studies in inflammation started in the past century, when neutrophil stiffening stimulated with chemoattractants, 14 granulocytes cortical tension, 251 and neutrophil kinetics, [252][253][254] among others were described. Since then, further discoveries in diseases have…”
Section: Inflammatory Diseasesmentioning
confidence: 99%